Encyclopedia of Inorganic Chemistry 2005
DOI: 10.1002/0470862106.ia318
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance (NMR) Spectroscopy of Inorganic/Organometallic Molecules

Abstract: NMR spectroscopy is an indispensable spectroscopic tool for the characterization of inorganic compounds. This contribution provides a guide to the application of recent advances in high‐resolution, solid‐state, and high‐pressure NMR spectroscopic methods to organometallic/inorganic molecules and solids. The topics covered include methods for the determination of structure, intermolecular interactions, solid‐state organization, reaction kinetics, and diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 114 publications
5
13
0
Order By: Relevance
“…The cyclopentenyl ligand bridges one of the metal-metal edges in a µ,η 1 :η 2 manner. This bonding mode has been previously encountered, for example, in Os 4 (µ-H) 3 (CO) 11 -(µ,η 1 :η 2 -C 6 H 9 ), [2b,18] Os 4 (µ-H) 3 (CO) 11 (µ,η 1 :η 2 -CHCHPh), [19] Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCHCH 2 CH 3 ), Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCH 2 ), and Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCHPh).…”
Section: Thesupporting
confidence: 55%
See 2 more Smart Citations
“…The cyclopentenyl ligand bridges one of the metal-metal edges in a µ,η 1 :η 2 manner. This bonding mode has been previously encountered, for example, in Os 4 (µ-H) 3 (CO) 11 -(µ,η 1 :η 2 -C 6 H 9 ), [2b,18] Os 4 (µ-H) 3 (CO) 11 (µ,η 1 :η 2 -CHCHPh), [19] Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCHCH 2 CH 3 ), Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCH 2 ), and Os 3 (µ-H)(CO) 10 (µ,η 1 :η 2 -CHCHPh).…”
Section: Thesupporting
confidence: 55%
“…Furthermore, a comparison of the hydride chemical shift for 2d (δ = -18.34 ppm) with that reported for the tetraosmium analogue, Os 4 (µ-H)(CO) 9 (µ-CO) 2 (η 5 -Cp*) (δ = -20.71 ppm), [9] shows that replacement of the osmium atom at the apex of the tetrahedron with the relatively more electronegative ruthenium atom results in a decrease in electron density at the hydride. [10] Some of the reactions with the C 5 carbocyclic rings also afforded other minor products other than 2. The reaction of 1 with propylcyclopentane afforded, after TLC separation, unreacted 1, Os 3 (µ-H) 2 (CO) 10 (a decomposition product of 1), 2c, and another novel cluster Ru 2 Os 3 (µ-H) 2 (CO) 13 (µ-CO)(µ 3 ,η 5 :σ 2 -C 5 H 3 C 3 H 7 ) (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43,44] Disappearance of this signal in the spectrum of Zn(II) complex suggested that this proton had been lost due to coordination of oxygen atom to the metal ion. [45] The signal due to H 2 of Zn(II) complex appeared at very low magnetic field compared with that of ligand, suggesting the involvement of N 1 in the formation of complex. The protons of N (1) and N (2) in AHQMBSH and its Zn(II) complex resonated as a singlet at δ 10.74, δ 12.48 and δ 10.71, δ 12.47 ppm respectively.…”
Section: H Nmr Spectramentioning
confidence: 95%
“…All the quinoline protons shifted slightly downfield, except H 7 , which shifted slightly upfield. [45,46] a Zone of inhibition (mm) obtained upon subtraction of control (DMSO) ≈11.…”
Section: H Nmr Spectramentioning
confidence: 99%